The Implementation of PORPE Strategy for the Teaching of Descriptive Reading Text - Siti Susanti Nur Oktavia; Sueb Sueb (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Reading is Reading comprehension ability is very important to improve learning achievement, because it increases vocabulary, fluency and language proficiency in various subjects, thereby influencing all material and teaching in each subject. This research investigates the application of the PORPE strategy in comprehending descriptive reading texts and its impact on student comprehension using a mixed methods research approach. The data was collected using observation, pre-test and post-test. It can be seen in this research, that the PORPE strategy, which consists of the stages of predicting, organizing, training, practicing and evaluating, can significantly improve students' understanding and analysis of descriptive texts, develop critical thinking and reading skills, and encourage active participation. In this research found, that there was a significant increase in students' average scores after implementing the PORPE strategy, from 57.37 to 80.37, which showed a statistically significant difference in scores before and after treatment. The PORPE strategy improved students' reading comprehension and critical thinking skills by facilitating interactive learning, increasing understanding of descriptive texts and fostering students' positive contributions.